Generating Matrices and Fibonacci-Like Numbers - Sivaraman, Dr. R. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Among several classes of interesting numbers, Fibonacci numbers plays a significant role and these numbers very often turns up in several branches of Science, Engineering and Technology. Considering two by two square matrices whose entries are Fibonacci and Fibonacci like sequence numbers, we investigate the integral powers of such matrices and prove interesting results concerning them. Finally, the limiting cases of entries of nth power of such matrices are derived.